2021
DOI: 10.1101/2021.12.17.473232
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Music-selective cortex is sensitive to structure in both pitch and time

Abstract: Converging evidence suggests that neural populations within human non-primary auditory cortex respond selectively to music. These neural populations respond strongly to a wide range of music stimuli, and weakly to other natural sounds and to synthetic control stimuli matched to music in many acoustic properties, suggesting that they are driven by high-level musical features. What are these features? Here we used fMRI to test the extent to which musical structure in pitch and time contribute to music-selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 129 publications
(232 reference statements)
0
1
0
Order By: Relevance
“…Several studies have now shown that the rostral recognition "what" pathway, seen for intelligibility in speech, is not only seen for speech: music and other identifiable environmental sounds also recruit the anterior temporal lobes in humans. There is compelling evidence that sound recognition is processed by parallel and distinct streams within these anterior fields (Norman-Haignere et al, 2015, 2022Boebinger et al, 2021). This strongly suggests that while speech may often appear to dominate in these regions, that may be a function of the predominance of studies that focus on speech, and of the well-established speech processing problems that arise due to damage in left middle temporal artery territory.…”
mentioning
confidence: 99%
“…Several studies have now shown that the rostral recognition "what" pathway, seen for intelligibility in speech, is not only seen for speech: music and other identifiable environmental sounds also recruit the anterior temporal lobes in humans. There is compelling evidence that sound recognition is processed by parallel and distinct streams within these anterior fields (Norman-Haignere et al, 2015, 2022Boebinger et al, 2021). This strongly suggests that while speech may often appear to dominate in these regions, that may be a function of the predominance of studies that focus on speech, and of the well-established speech processing problems that arise due to damage in left middle temporal artery territory.…”
mentioning
confidence: 99%